The role of information in agricultural technology adoption: Experimental evidence from rice farmers in Uganda - Van Campenhout, Bjorn; Walukano, Wilberforce; Nattembo, Fiona; Nazziwa-Nviiri, Lydia; Blom, Jaap (International Food Policy Research Institute, 2017)
Optimal decision making among the poor is often hampered by a lack of critical pieces of information, false beliefs or wrong perceptions. This paper investigates the role of information deficiencies in the decision to use modern inputs and adopt recommended agronomic practices among rice farmers in Uganda. Using field experiments, we tested whether the provision of technical information concerning the existence and use of modern inputs and practices affects awareness and adoption of these technologies as well as farm production. In addition, we tested whether providing information aimed at changing the perception of returns on such intensification investments leads to different outcomes.